Можливі шляхи зменшення викидів СО2 енергоустановками у довкілля - Грінченко, Дмитро; Брикайло, Роман (Видавництво Національного університету «Львівська політехніка», 2001)
Shown the possible troop landings underestimation ways into СО2 atmosphere. In that number by dint of СО2 selection from fuel gases with following his use in special burner for receipt of new CO fuel and to hydrogen.